A study exploring the perceived experiences of women who dropped out of GED preparation programs - Holt, Cora Ellen (Kansas State University, 2014)
Significant numbers of women drop out of GED preparation programs. This phenomenological study used interviews and demographic surveys to learn how 12 women perceived their experiences of dropping out of GED programs. Possible selves theory and McClusky’s theory of margin provided the theoretical framework for this research. Possible selves theory examined how women’s past, present, and future selves were considered in their experience of the phenomenon, while theory of margin was used to look at the network of challenges and supports present in their lives. This study found that at the time the women dropped out of GED programs: (a) they no longer believed they could achieve their desired future selves, (b) past choices continued to adversely affect them, (c) their burdens far exceeded their resources, (d) they identified the status quo as their feared possible selves, and (e) they believed that having a tutor would have enabled them stay in GED classes. The study recommends: (a) introducing theory of margin and possible selves to students as tools for taking stock and planning for educational success, (b) forming community volunteer tutoring networks, and (c) recording dropout numbers within GED programs to illustrate the need for additional funds. This population is marginalized because they become invisible to society and GED preparation programs when they stop attending.
Keywords: Women; Dropout; GED; Possible selves; Margin; Adult Education (0516); Educational leadership (0449); Education, General (0515)